Product redesign by topology optimization for additive manufacturing process - Salima, Wongani Clement Kizito (2021)
This research evaluates an Alcoa bearing bracket commonly used on control surfaces of aircraft, The study seek to redesign the Alcoa bracket to minimize the weight while fitting in the same target design envelope and meeting (he technical requirements and this is achieved by using the Topology Optimization (TO) technique. The objectives of this research are; to obtain the best TO model based on strength to weightratio, von Mises stress,displacement, mass, and factor of safety by varying weight retentions between 10%-70% using solidThinking Inspir, then to optimize build orientation for the minimum amount of support structures using Fusion 360, and to obtain the required geometric compensations of the Alcoa bracket by usingan Artificial Neural Netwark (ANN) tool in MATLAB o produce a more aceurate bracket by controlling deformations oceurring due to residual stresses after the Additive Manufacturing (AM) heating process. The methodology has three sections, the first scction deals with pre-analysis and topology optimization, where three materials (15~SPH Steel, Ti6AI4V ELI-0406, and Ti-6AI-2Sn-4Zr-6Mo) were compared, and one material was selected for the design process based on material physical properties then topology: optimization process was performed to oblain a design with excellent strength to weight ratio, von Mises stress, displacement, mass, and factor of safety. The second section deals with build orientation optimization in Fusion 360 to obtain the minimum amount of support structure during AM process. The third section deals with the ANN tool to make the required geomeric compensations on the bracket which help to control deformation arising due to the AM heating process, a conformity check was conducted to validate and show the, improvements achieved on the bracket after the ANN tool was implemented then the section. finalizes with 3D printing of the bracket just to visualize the outcome of the TO process since the study's focus is entirely on computer simulations and not experiments. In the results, Ti-6AI-25n-4Zr-6Mo was selected as the material to use for the design process. the results also selected a 40% volume retention as the best model amongst the seven (7) iterations conducted, while the other results selected Rank I as the best-optimized build orientation amongst the thirteen (13) Ranks, while in the ANN results, it was found that before compensation, the conformity score of the deformed nodes after AM simulation was 76312 for bracket with Cartesian mesh and 85,196 for bracket with Layered tetrahedral mesh while the conformity score after the AM simulation of the compensated bracket the conformity was 89.726 on Cartesian mesh bracket and 94.342 on Layered tetrahedral mesh bracket showing that there was an increase in conformity after the compensation. Finally, the TO model was printed by a 3D printer and it showed similar dimensions to the bracket’s CAD model. In conclusion, the research selected a 40% volume retention using Ti-6Al-2Sn-47r-6Mo, also selected Rank 1 build orientation, and achieved 59.75% and 61.784% reduction in conformity error for Cartesian and Layered tetrahedral mesh respectively.